Phenotypic Variability and Selection of Candidate Plus Trees (CPTs) of Terminalia chebula in Western Vidarbha Region of Maharashtra, India - Deshmukh, A.J.; Upadhyaya, Kalidas; Taide, Y. B.; Deshmukh, A.G. (Indian Journal of Agroforestry, 2026)
Hirda (Terminalia chebula Retz.) is one of the most important medicinal plants which has got the focus of the world in past few years due to the use of its fruits in ayurvadic medicines. Because of its increasing demands in the holistic health care system, the selection of high yielding genotypes with high value of phytoconstituents is paramount to ensure sustained supply of quality fruits of the species. the variability studies in T. chebula which is a precursor to the selection of high yielding genotypes, are still in initial stage. The present study was carried out to assess the phenotypic variability and for the selection of Candidate Plus Trees (CPT’s) of T. chebula in Western Vidarbha region of Maharashtra. The extensive survey was conducted in all the five districts (i.e. Akola, Amravati, Buldhana, Yavatmal and Washim) of Western Vidarbha region of Maharashtra, but, T. chebula was found only in Akola and Amravati districts (Malghat area). All together twenty-eight candidates plus trees (CPT’s) were selected from the study area. All these fruit samples were analyzed for its phenotypic variability and fruit yield. On the basis of phenotypic variability twenty-eight trees were selected from the Western Vidarbha region of Maharashtra. The maximum fruit yield was recorded in TC-2 (84kg) followed by TC-15 (80kg) and TC-17 (79kg) while maximum fruit and pulp weight was recorded in TC-6 (38.40gm and 25.70gm) followed by TC-24 (24.17 and 16.87gm) and TC-19 (23.45 and 15.58gm). The smallest size fruits and pulp was recorded in TC-12 (5.12 and 3.06gm) fallowed by TC-8 (8.84 and 5.32gm) and TC-9 (9.06 and 5.87gm). The maximum tree height was recorded in TC-2 (21.50m) followed by TC- 10 (17.50m) and TC-12 (16.60m). While maximum DBH was recorded in genotype TC-15 (84cm) followed by TC-22 (82 cm) and TC-15 (81 cm). The selected CPT’s can be utilized to produce quality planting material for farmers to plant this high value multipurpose agroforestry tree species on the farm boundary, to get extra income as there is a high demand for its fruits.